Establishing appropriate sample size for developing and validating a questionnaire in nursing research - Gunawan, Joko; Marzilli, Colleen; Aungsuroch, Yupin (Belitung Raya Foundation, Indonesia, 2021)
The number thirty is often used as the sample size in multiple questionnaires and identified as appropriate for validation of nursing research. However, this is not the best tool or strategy for sample size selection for development and validation, and this often causes immediate rejections of manuscripts. This editorial aims to provide an overview of the appropriate sample size for questionnaire development and validation. The article is the amalgamation of technical literature and lessons learned from our experiences in developing, validating, or adapting a number of questionnaires.